Synthesis of Nanocomposite Materials Based on TiO2 Nanotubes and Polymethylene Naphthylene Sulfonate and their Electrophysical Properties - Karshibayev, Jakhongir; Djumagulov, Sherzod; Ruzimurodov, Olim; Nurmatov, Doston; Mansurov, Tolmas; Akhmedov, Sultan; Otakuziyeva, Vazira; Askarova, Nilufar (Asian Journal of Chemistry, 2025)
In this study, nanocomposite materials composed of titanium dioxide (TiO2) nanotubes and polymethylene naphthylene sulfonate (PMNS) were successfully synthesized and extensively characterized. TiO2 nanotubes were fabricated via electrochemical anodization in an ethylene glycol-based electrolyte containing ammonium fluoride, under varying voltage and time conditions. Scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR) analyses confirmed the formation of well-aligned, porous nanotube structures with diverse lengths and morphologies. A detailed investigation was carried out to evaluate the influence of anodization voltage (ranging from 20 to 80 V) and electrolyte composition on the height and surface uniformity of the nanotubes. PMNS was synthesized through the sulfonation and subsequent polycondensation of b-naphthalene sulfonic acid with formaldehyde under precisely controlled thermal and stoichiometric conditions. The structural characteristics of the resulting polymer were examined using IR spectroscopy, complemented by quantum chemical calculations, including HOMO-LUMO energy gap analysis and charge distribution profiling. The TiO2 nanotubes were then combined with PMNS through an electrochemical polymerization technique to create the final nanocomposites. Their electrochemical behaviour was studied using voltammetric techniques, revealing that both the electrolyte composition and nanotube architecture significantly affect the electrical conductivity. These composites exhibited distinctive p-type and n-type semiconducting behavior, which is strongly influenced by the polymer/oxide interface. Overall, the TiO2-PMNS nanocomposites demonstrated promising electrical performance, suggesting their potential application in smart electrochemical devices, supercapacitors, and sensor technologies. This work contributes to the development of advanced nanomaterials based on semiconducting polymers and provides valuable insights into the structure-property relationships critical for next-generation electronic systems.